The prevalence of anti‐K in Canadian prenatal patients. Issue 6 (13th May 2015) - Goldman, Mindy; Lane, Debra; Webert, Kathryn; Fallis, Robert
Abstract : BACKGROUND: Anti‐KEL1(K) is a major cause of hemolytic disease of the fetus and newborn. We utilized data from prenatal testing of patients in Western Canada to determine the frequency of anti‐K. In Manitoba, we evaluated the frequency of transfusion as the likely cause for alloimmunization. We reviewed international practices to prevent alloimmunization. STUDY DESIGN AND METHODS: Prenatal patients undergo antibody screening using an automated testing platform and uniform testing algorithm. Data on the frequency of antibodies, transfusion history, and donor K typing were extracted from the relevant databases at Canadian Blood Services. National standards were reviewed with the help of local experts. RESULTS: Anti‐K was found in 397 of 390, 193 patients from 2011 to 2013 (1.02 per 1000) and was the second most frequent antibody after anti‐E. In Manitoba, 26 of 75 (35%) anti‐K patients had received transfusions in the province since 2001; 14 of the 26 (54%) had received at least one K+ RBC unit and three had received all K– units, while in nine, donor K typing was incomplete. Only eight of the 26 had previous pregnancies, three with K+ partners. International practice varies; however, prophylactic use of matched or K– units is standard in many European countries. CONCLUSIONS: Anti‐K was found in 0.1% of prenatal patients. Although our data on the history of transfusion are incomplete, they demonstrate that transfusion with a K+ unit is a major cause of alloimmunization. Given advances in phenotyping and genotyping technologies, prophylactic matching should be considered in Canada.